PERBEDAAN PENGARUH HALF SQUAT JUMP DAN ISOMETRIC SQUAT TERHADAP PENINGKATAN DAYA LEDAK OTOT TUNGKAI PEMAIN BASKET - Trioclarise, Rovika; Kurniawan, Ganesa Puput Dinda; Aristawati, Nurul Izzah (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Background: athlete does not perform regular training within 2 weeks, there will be a reduction in muscle mass followed by a decrease in muscle explosiveness. Muscle explosive power is a persons ability to do business with maximum strength in the shortest time. Ways to increase muscle explosive power include half squat jump and isometric squat exercises. Research Objectives: to determine the difference in the effect of half squat jumps and isometric squats on increasing the explosive power of the leg muscles of Basketball Players at SMAN 11 Bekasi. Methods: This research conducted quasi experimental research design through two groups pre-post test, the sample was selected by purposive sampling method with a total sample of 12 people in each group in half squat jump group and isometric squat group. Results: the results of the paired t-test in the half squat jump and isometric squat groups had an effect on muscle explosive power, but the half squat jump group had a higher average. The independent t-test in the group after being given the intervention showed that there was a difference in the effect between giving the half squat jump and isometric squat.. Conclusion: There is a difference in results between giving half squat jump and isometric squat training.